Frequency of Anemia in Patients with Heart Failure Admitted to Cardiology Unit of Tertiary Care Hospital - Jamil Ur Rahman; Saghir, Tahir; Zaman, Shahid; Idrees, Muhammad; Shakil, Muhammad; Zada, Shakir (Indus Journal of Bioscience Research, 2025)
Background: Anemia is a common but often underdiagnosed comorbidity in patients with heart failure (HF), contributing to increased morbidity, hospitalizations, and reduced quality of life. Objective: This study aimed to determine the frequency of anemia among HF patients admitted to a tertiary care cardiology unit and explore associated clinical factors. Methods: This cross-sectional study was conducted at the Department of Cardiology, NICVD, Karachi, from 11 Feb 2025 to 11 May 2025. A total of 191 patients aged 40–80 years with a confirmed diagnosis of HF were enrolled using non-probability consecutive sampling. Patients with chronic kidney disease, blood dyscrasias, recent transfusions, malignancy, or iron supplementation were excluded. Hemoglobin levels were assessed to determine anemia status. Results: Among 191 patients, 89 (46.6%) were found to have anemia. Anemia was significantly more common in patients aged ≥60 years (p = 0.01), with longer disease duration (p = 0.02), BMI <25 kg/m² (p = 0.03), and NYHA class III–IV (p < 0.001). Although female patients had a higher prevalence of anemia, the association was not statistically significant (p = 0.08). Conclusion: Anemia is highly prevalent among heart failure patients, particularly in those who are elderly, underweight, or have advanced functional class or chronic disease. Routine screening and timely management of anemia should be integrated into heart failure care protocols to improve patient outcomes.